2011
DOI: 10.5539/ijef.v3n6p16
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Effects in Emerging Stock Markets - The Case of Iran Stock Market

Abstract: In view of the mixed empirical results in the literature, this paper assesses the extent of asymmetric volatility effects in the Iranian stock market as an emerging stock market, using a variety of nonlinear autoregressive conditional heteroskedasticity specifications. Tests based on standardized residuals from a fitted GARCH model suggest a lack of asymmetric effects in the dynamic volatility of the Iranian stock market. Empirical analyses with asymmetric GARCH models also reject the hypothesis of asymmetric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 21 publications
1
10
0
Order By: Relevance
“…This reveals the presence of leverage effect in the Nigerian stock market whereby stock returns volatility increases with bad news but the volatility reduces with good or positive news. This is in tandem with Ederington& Lee (1993,1996) [38], Andersen and Bollerslev (1996) [32], Almeida, et al (1997) [39] and Chen et al (1999) who posit that the release of public information is an important driver of market volatility. [3]…”
Section: Resultsmentioning
confidence: 57%
See 1 more Smart Citation
“…This reveals the presence of leverage effect in the Nigerian stock market whereby stock returns volatility increases with bad news but the volatility reduces with good or positive news. This is in tandem with Ederington& Lee (1993,1996) [38], Andersen and Bollerslev (1996) [32], Almeida, et al (1997) [39] and Chen et al (1999) who posit that the release of public information is an important driver of market volatility. [3]…”
Section: Resultsmentioning
confidence: 57%
“…Andersen, Bollerslev, Diebold and Ebens, (2001) note that little is known about the distribution of correlation of returns on individual stocks. [32] According to them, if leverage effect is the cause of the volatility asymmetry in individual stock, then a change in financial leverage may also affect the covariance between different stocks, which in turn is likely to impact the correlations. Hence, it was noted that the different multivariate ARCH models estimated in Kroner & Ng (1998) result in significant asymmetric effect in the conditional covariance matrices for weekly returns on well diversified large and small portfolios of stock.…”
Section: Literature Reviewmentioning
confidence: 99%
“…When the sum is significantly less than one, volatility shock will not last for a long time but when it is significantly close to one, volatility shocks can last for some time. When the sum is one, volatility shock will last for the indefinite future (Oskooe & Shamsavari, 2011). Given absence of normal distribution in Section 3.2, the shape parameter ( c ) was modelled using the GED.…”
Section: Data Descriptive Statistics and Methodologymentioning
confidence: 99%
“…However, empirical evidence from some frontier markets 1 has shown that asymmetric responses of volatility to news are diverse. While some studies document evidence of good news propelling volatility more than bad news, few other studies have shown absence of volatility asymmetry (see, for example, Ogum et al, 2005; Saleem, 2007; Oskooe & Shamsavari, 2011; Khan et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…ARCH family models have been applied to encapsulate different characteristics of stock markets' conditional returns and variances. Using non-linear GARCH models, Iranian capital market assessed to have the same impact of good and bad news of equal size and the absence of asymmetric volatility [26]. By employing ARCH and GARCH models, Midhra found time-varying volatility of Indian stock market to be more sensitive to bad news from 1991 to 2009.…”
Section: Introductionmentioning
confidence: 99%